Strength parameters and their inter-relationship for limestone of Cherat and Kohat areas of Khyber Pakhtunkhwa - Tahir, Muhammad; Mohammad, Noor; Din, Feroz (Journal of Himalayan Earth Sciences, 2011)
Determination of various strength parameters like Uniaxial Compressive Strength, Uniaxial Tensile Strength and Point Load Strength Index are addressed in the following research. International Society of Rock Mechanics (ISRM) standard procedure for the determination of above-mentioned parameters was adopted. Samples of limestone from Kohat and Cherat areas of Khyber Pakhtunkhwa province of Pakistan were tested for uniaxial compressive strength, tensile strength and point load index. Sixty samples were analyzed for determination of these parameters and results were plotted against each other to establish relationships between uniaxial compressive strength with tensile strength and point load index. A comprehensive review of various relationships established for same rock condition from literature has been presented. Findings of the research constitute major part of the paper and results indicate that weak correlation exists between uniaxial compressive strength with tensile strength and point load index for limestone from Kohat and Cherat. The analyses of data for various strength parameters and relationships derived so far constitute major part of this research paper.